Cost and cost threshold analyses for 12 innovative US HIV linkage and retention in care programs. Issue 9 (1st September 2016) - Jain, Kriti M.; Maulsby, Catherine; Brantley, Meredith; ,; Kim, Jeeyon Janet; Zulliger, Rose; Riordan, Maura; Charles, Vignetta; Holtgrave, David R.
ABSTRACT: Out of >1, 000, 000 people living with HIV in the USA, an estimated 60% were not adequately engaged in medical care in 2011. In response, AIDS United spearheaded 12 HIV linkage and retention in care programs. These programs were supported by the Social Innovation Fund, a White House initiative. Each program reflected the needs of its local population living with HIV. Economic analyses of such programs, such as cost and cost threshold analyses, provide important information for policy-makers and others allocating resources or planning programs. Implementation costs were examined from societal and payer perspectives. This paper presents the results of cost threshold analyses, which provide an estimated number of HIV transmissions that would have to be averted for each program to be considered cost-saving and cost-effective. The methods were adapted from the US Panel on Cost-effectiveness in Health and Medicine. Per client program costs ranged from 1109.45 to 7602.54 from a societal perspective. The cost-saving thresholds ranged from 0.32 to 1.19 infections averted, and the cost-effectiveness thresholds ranged from 0.11 to 0.43 infections averted by the programs. These results suggest that such programs are a sound and efficient investment towards supporting goals set by US HIV policy-makers. Cost-utility data are pending.